2020
DOI: 10.2298/sos2002135l
|View full text |Cite
|
Sign up to set email alerts
|

Formation of anorthite containing cordierite materials through reaction sintering kaolin, MgO and CaO precursors

Abstract: The effect of CaO on cordierite formation from kaolin-MgO-CaO powder mixtures, milled for 5 h and reaction sintered for 2 h in the temperature range 900-1400?C, was investigated. Phases formed in the developed materials were characterized by x-ray powder diffraction method (XRD) and Raman spectroscopy. Non-isothermal differential thermal analysis (DTA) and thermogravimetric (TG) experiments were performed from room temperature to 1400?C, at heating rates from 20 to 40?C/min. Activation energi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…These starting materials have been processed by employing different methods such as sintering of powder mixtures, mechanochemical treatments and sol-gel procedures [15][16][17]. In recent years, a great deal of research has been devoted to the development of new technical ceramics, using raw materials instead of industrial chemicals due to the lower price of raw materials available [18,19]. Kaolin, as a good source of silicon and aluminium [20] has been reported as aproper starting, raw material for production of anorthite ceramics owing to its abundances and relatively low price.…”
Section: Introductionmentioning
confidence: 99%
“…These starting materials have been processed by employing different methods such as sintering of powder mixtures, mechanochemical treatments and sol-gel procedures [15][16][17]. In recent years, a great deal of research has been devoted to the development of new technical ceramics, using raw materials instead of industrial chemicals due to the lower price of raw materials available [18,19]. Kaolin, as a good source of silicon and aluminium [20] has been reported as aproper starting, raw material for production of anorthite ceramics owing to its abundances and relatively low price.…”
Section: Introductionmentioning
confidence: 99%
“…Algeria has large deposits of kaolin raw materials, particularly in the east of the country. Several work projects were carried out in recent years to assess the Algerian kaolin properties such as formation of anorthite containing cordierite materials throught reaction sintering kaolin, MgO and CaO precursors [7], preparation and microfiltration membranes and their supports using kaolin (DD 2 ) and CaCO 3 [8], elaboration of tubular supports for membranes filtration based on kaolin DD 3 and lime extracted from limestone [9]. Chargui et al [10] showed that kaolin, whose main constituent is kaolinite (Al 2 Si 2 O 5 (OH) 4 ), undergoes successive structural and microstructural transformations during its firing.…”
Section: Introductionmentioning
confidence: 99%